Incentive schemes from the employees' perspective - Chin, Sook Kwan (2008)
This research investigates the types of incentives that employees value and highlights those that affect employee motivation. A questionaire is constructed based on a literature review of the topic in question and it is given to subjects on a random basis. This project then provides suggestions as to how employee incentive systems can be improved. The hypothesis is that an improved incentive system will lead to higher employee motivation which in turns affect organisational productivity.